THE IMPACT OF CHILDHOOD TRAUMA ON BORDERLINE PERSONALITY DISORDER - Nurina Hadini Hasya (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Introduction – Currently borderline personality disorders has become a major focus of clinical findings. Borderline personality is defined as a disruption to the criteria for emotional instability, blurred identity, and spontaneous behavior that begins with adulthood. Usually, patients with borderline personality disorders have a trauma in their childhood where that trauma that makes their personality disturbed. Methods – The author makes a literature review of the effect of trauma in childhood on borderline personality disorder based on literature that has been published and had correlation. Results – Trauma that occurred at the time children will carry over to adulthood and affect the person's view about himself and others. Childhood trauma can include physical violence, sexual violence, abuse, emotional abuse, or perhaps just witnessing violence between families. Discuss – There is an assumption that there is a relationship associated with abuse in childhood, difficulty controlling emotions. That is show that neglected emotions can be attributed to a lack of strategies for emotional regulation. This is possible argued that diverse types of traumas may influence the degree of difficulty in regulating different emotions. Conclusion – there is a significant correlation with trauma in the childhood and borderline personality disorder. It is known that to prevent the occurrence of BDP, can be done with forget about childhood trauma. In summary, childhood trauma, is connected to unstable management of emotion control. Moreover, difficulty in managing the emotions have a big role between abusing emotion and acute borderline personality disorder.     Keywords: borderline personality disorder, childhood trauma, emotion.